2020
DOI: 10.3390/insects11070423
|View full text |Cite
|
Sign up to set email alerts
|

Wavelength-Specific Behavior of the Western Flower Thrips (Frankliniella occidentalis): Evidence for a Blue-Green Chromatic Mechanism

Abstract: The western flower thrips (Frankliniella occidentalis) is a serious pest in horticulture, feeding on leaf tissue and floral resources. Blue and yellow sticky traps are commonly used for monitoring and control in greenhouses. The mechanisms underlying the color preferences are largely unknown. The use of light-emitting diodes (LEDs) is a promising approach to increase the attractiveness of visual traps and to study the color choice behavior in insects. The color preferences of F. occidentalis were syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
34
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 34 publications
7
34
0
1
Order By: Relevance
“…Although the B:Y ratios changes only slightly between Stikem and D41 on yellow plates (see results: 2%) it has been shown that small changes in composition can lead to major shifts in behaviour 30 . The recently published “blue-green opponency” of western flower thrips 29 is a colour opponency that may play a role even though our thrips strain responds in general better to yellow, which is considered a bright supernatural green to insects. While Stukenberg et al 29 showed that blue and green LEDs were attractive, addition of green LED to blue LED decreased attraction compared to its single components.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the B:Y ratios changes only slightly between Stikem and D41 on yellow plates (see results: 2%) it has been shown that small changes in composition can lead to major shifts in behaviour 30 . The recently published “blue-green opponency” of western flower thrips 29 is a colour opponency that may play a role even though our thrips strain responds in general better to yellow, which is considered a bright supernatural green to insects. While Stukenberg et al 29 showed that blue and green LEDs were attractive, addition of green LED to blue LED decreased attraction compared to its single components.…”
Section: Discussionmentioning
confidence: 99%
“…The recently published “blue-green opponency” of western flower thrips 29 is a colour opponency that may play a role even though our thrips strain responds in general better to yellow, which is considered a bright supernatural green to insects. While Stukenberg et al 29 showed that blue and green LEDs were attractive, addition of green LED to blue LED decreased attraction compared to its single components. We measured increased reflection of blue and green on yellow sticky plates with Stikem and decreased reflection of green on blue plates with Stikem compared to D41 (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The behavior of thrips to green flowers might also be explained by this 'settling behavior' of insects. Western flower thrips might not only respond to the flower colors, but most likely also respond to the vegetative, and thus, corresponding green parts of a plant (Stukenberg et al, 2020).…”
Section: Attractiveness Of Flowers To Frankliniella Occidentalismentioning
confidence: 99%
“…It is not clear whether Western flower thrips show a preference for a certain shape or color of flowers. Most studies investigating the influence of color use only colored traps (Otieno et al, 2018;Stukenberg et al, 2020).…”
Section: Introductionmentioning
confidence: 99%